2019
DOI: 10.1002/jbm.a.36643
|View full text |Cite
|
Sign up to set email alerts
|

Participation of integrin β3 in osteoblast differentiation induced by titanium with nano or microtopography

Abstract: The major role of integrins is to mediate cell adhesion but some of them are involved in the osteoblasts–titanium (Ti) interactions. In this study, we investigated the participation of integrins in osteoblast differentiation induced by Ti with nanotopography (Ti‐Nano) and with microtopography (Ti‐Micro). By using a PCR array, we observed that, compared with Ti‐Micro, Ti‐Nano upregulated the expression of five integrins in mesenchymal stem cells, including integrin β3, which increases osteoblast differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 43 publications
(106 reference statements)
2
26
0
Order By: Relevance
“…GSEA revealed that the integrin pathway and cytoskeletal organisation were enriched in MSCs. One study reported that integrin enhanced the differentiation of MSCs into osteoblast [ 53 ]. Other studies also confirmed the roles of integrin pathway in MSC differentiation [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…GSEA revealed that the integrin pathway and cytoskeletal organisation were enriched in MSCs. One study reported that integrin enhanced the differentiation of MSCs into osteoblast [ 53 ]. Other studies also confirmed the roles of integrin pathway in MSC differentiation [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the participation of the integrin signaling pathway, through FAK, in response of osteoblastic cells to different surface topographies. [9][10][11][12][13][14][15][16] Thus, the role of specific FAK inhibitors in the osteogenic potential of cells on Ti surfaces is an interesting research topic. The present study aimed to investigate the participation of FAK in interactions between osteoblastic cells and Ti surfaces with different topographies by using a specific FAK inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…Martinez et al (2018) showed that, when osteoblasts were grown into a nanotopography, greater cell spreading, proliferation, and viability, as well as increased expression of two proteins involved in the initial osseointegration process were observed, when compared with a surface treated by double etching alone. Furthermore, other studies depicted the benefits of NANO surface (de Oliveira, Zalzal, Beloti, Rosa, & Nanci, 2007; Jimbo et al, 2011; Longo et al, 2016; Lopes et al, 2019b; Lopes et al, 2020). In the present study, gene expression (Runx2, Alp and Opn) and micro‐CT (BV/TV, BIC, BS/BV and Po.To) analysis revealed the superiority of NANO surface when compared to machined and DAE (data as a function of implant surface).…”
Section: Discussionmentioning
confidence: 95%